2014
DOI: 10.1007/s40263-014-0208-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Nicotinic Cholinergic System to Treat Attention-Deficit/Hyperactivity Disorder: Rationale and Progress to Date

Abstract: Attention-Deficit/Hyperactivity Disorder (ADHD) is a common, chronic neurobehavioral disorder related to clinically significant levels of inattention, hyperactivity and/or impulsivity. ADHD begins in childhood and symptoms persist into adulthood for the majority of those with the disorder. Associated features of ADHD include emotion dysregulation and cognitive impairments which contribute to the considerable functional impairments in this disorder. Current approved treatments are reasonably effective however a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 84 publications
(112 reference statements)
0
22
0
Order By: Relevance
“…These molecular actions may also explain varenicline’s efficacy in reducing withdrawal, given that nicotine withdrawal is associated with reductions in basal dopamine levels in the striatum (Zhang et al, 2012). Overall, because nicotine has been linked to reduction of ADHD symptoms (Conners et al, 1996; Potter et al, 2014), it is possible that varenicline may contribute to successful decreases smoking in individuals with high HI, partially through an effect on reducing ADHD symptoms in concert with changing smoking behavior. Future research examining ADHD symptom dimensions over the course of varenicline treatment is necessary to shed light on this hypothesis.…”
Section: 0 Discussionmentioning
confidence: 99%
“…These molecular actions may also explain varenicline’s efficacy in reducing withdrawal, given that nicotine withdrawal is associated with reductions in basal dopamine levels in the striatum (Zhang et al, 2012). Overall, because nicotine has been linked to reduction of ADHD symptoms (Conners et al, 1996; Potter et al, 2014), it is possible that varenicline may contribute to successful decreases smoking in individuals with high HI, partially through an effect on reducing ADHD symptoms in concert with changing smoking behavior. Future research examining ADHD symptom dimensions over the course of varenicline treatment is necessary to shed light on this hypothesis.…”
Section: 0 Discussionmentioning
confidence: 99%
“…The self-medication hypothesis is also endorsed by the results obtained with the nicotine analogues bupropion and varenicline (Potter, Schaubhut, & Shipman, 2014;Ferris & Beaman, 1983;Mihalak, Carroll, & Luetje, 2006;Rhodes et al, 2012) which have been successfully applied as smoking cessation aid (Hurt et al, 1997;Aubin et al, 2008). Bupropion showed beneficial effect during treatment of ADHD.…”
Section: Self-medicationmentioning
confidence: 96%
“…Also, it has been demonstrated that perinatal choline supplementation may attenuate alcohol-related behavioral changes by influencing cholinergic systems (Monk et al, 2012). For ADHD, there are evidences that point to a role of the cholinergic system in ADHD cognitive dysfunction (Potter et al, 2006; Sarter and Paolone, 2011) and that emphasize the relevance of the therapeutic potential of nicotinic cholinergic agents for their treatment (Potter et al, 2014). Therefore, it is necessary to develop more enhanced understanding of the nicotinic cholinergic system and its role in ADHD (Childress and Sallee, 2014).…”
Section: Key Neurotransmitters Systems Are Affected In Pae and Adhdmentioning
confidence: 99%